A Study on the Methods to Prevent Soil Toxicology: Methods and Strategies for Preventing Soil Toxicology and Pollution (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Soil pollutants can be solid, liquid or gaseous. They deteriorate the quality and mineral content of soil and disturb the biological balance of organisms in the soil. Causes of soil pollution include an increase in urbanization, domestic waste, dumping industrial waste on soil and improper agricultural activities. You can prevent soil pollution by minimizing or eliminating waste at the source and substituting nontoxic options for hazardous materials.Plants require soil nutrients such as nitrogen, calcium and phosphorous for growth and development. Also, crops come under attack from rodents, insects and bacteria, so farmers require pesticides to protect the plants. The use of fertilizers and pesticides in agriculture, however, leads to other problems. Some raw materials can contaminate the soil. For instance, copper and boron in fertilizers, and organochlorine in pesticides, can harm the environment and create health risks when products are used in wrong proportions or over a long period of time.To prevent such damage, farmers should use composted manure and bio-fertilizers -- biologically active products such as algae and bacteria that can help initiate nitrogen fixation in soil. Biological methods of pest control such as importation – introducing a pest’s natural enemy in a location where they do not naturally occur — also minimize soil pollution.